Pemikiran Mohammed Arkoun Dalam Penafsiran Kontemporer - Misnawati Misnawati; Samsul Bahri; Muhammad Nuzul Abrar (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Mohammed Arkoun is a scholar who provides another breakthrough as an alternative in understanding the Qur'an, although he is not the first, who propose the Qur'an ѕahīh fī kulli zamān wa makān. This is idea has motivated comtemporer scholar deeply discuss on the Qur’anic discourse. Arkoun, who is a neo-modernist thinker, tried to suggest the hermeuneutic approach as a wayout solution in overcoming problems related to the methodology of interpreting the Qur'an. Some of his thoughts conveyed were contradictory to the thought of other Muslim figures. He is one og the thinkers who are in the path of